Pengaruh Team Status, Biaya Transfer dan Biaya Gaji Terhadap Market Value Pemain Sepak Bola Profesional (Studi Empiris Pada Himpunan Sepak Bola Yang Masih Berkompetisi dalam Liga Inggris Periode 2018-2019) - Aditya Putra, I Putu Wahyu; Devi, Sunitha (Universitas Pendidikan Ganesha, 2021)
This research aims to find out the effect of team status on the market value of professional football players, transfer fees on the market value of professional football players, and salary costs on the market value of professional football players. This research was a qualitative study with a total of 105 professional football players. The data was obtained from the transfermrkt site. The sample technique used was purposive sampling. The data used was secondary data and it was processed using the SPSS application. The results showed that the team status had a positive and significant effect on the market value of professional football players, transfer fees had a positive and significant effect on the market value of professional football players, and salary costs also had a positive and significant effect on the market value of professional football players.